PTH-085 The use of 5-asa in inflammatory bowel disease: national population based study. (22nd June 2015) - Chhaya, V; Saxena, S; Cecil, E; Subramanian, V; Curcin, V; Majeed, A; Pollok, R
Abstract : Introduction: 5-aminosalicylates (5-ASA) have a proven efficacy in induction and maintenance of ulcerative colitis (UC). The evidence that 5-ASAs have efficacy in the induction and maintenance of remission in Crohn's disease (CD) is weak and not supported by recent meta-analyses 1 or current guidelines. Our aim was to determine if patients with CD and UC were being appropriately prescribed 5-ASAs Method: We constructed an incident cohort of patients with CD and UC diagnosed between 1990 and 2009 using the Clinical Practice Research Datalink (CRPD), a validated research database representing an 8% sample of the UK population. We divided our cohort to compare patterns between era: era 1 (1990–1993), era 2 (1994–1997), era 3 (1998–2001), era 4 (2002–2005) and era 5 (2006–2009). We performed a Kaplan-Meier survival analysis to quantify the 3 year probability of receiving a 5-ASA. We identified patients with "prolonged 5-ASA use" defined as use for greater than 12 months duration to determine whether patients were inappropriately maintained on 5-ASAs for CD. We compared the proportion (number of users/total number within the era) of prolonged 5-ASA use between time periods using the 2-group proportion test. Results: In CD, there were 6997 patients who met our inclusion criteria. The 3 year cumulative probability of receiving a 5-ASA was 40.5% (95% CI: 35.9–45.4), 49.7% (95% CI: 45.7–53.8), 50.8% (95% CI: 48.0–53.6), 52.5% (95% CI: 50.1–54.9) and 61.8% (95% CI: 58.9–64.8) for era 1, 2, 3, 4 and 5 respectively. Prolonged oral 5-ASA use was prevalent throughout the study period in CD, although decreased between era 3 and era 5 from 59.2% to 47.2% (p < 0.001). In UC, there were 16, 512 patients who met our inclusion criteria. The 3 year cumulative probability of receiving a 5-ASA was 31.7% (95% CI: 29.3–34.3), 36.6% (95% CI: 34.3–39.0), 42.9% (95% CI: 41.0–44.7), 46.2% (95% CI: 44.6–47.8) and 55.4% (95% CI: 53.4–57.4) for era 1, 2, 3, 4 and 5 respectively. Prolonged oral 5-ASA use was increasing throughout the study period in UC, 43.3% to 53.0% between era 1 and era 4 (p < 0.001). Conclusion: In CD, 5-ASA use remains common with over 50% of patients receiving the medication, including maintenance therapy, despite a lack of evidence to support this clinical practice. In UC, 5-ASA use has increased appropriately although not all patients appeared to be maintained on these drugs. Disclosure of interest: None Declared. Reference: Ford AC, Kane S V, Khan KJ, Achkar J-P, Talley NJ, Marshall JK, Moayyedi P. Efficacy of 5-aminosalicylates in Crohn's disease: systematic review and meta-analysis. Am J Gastroenterol 2011;106:617–29